2020
DOI: 10.3390/nano10091717
|View full text |Cite
|
Sign up to set email alerts
|

Gold Nanoparticles Radio-Sensitize and Reduce Cell Survival in Lewis Lung Carcinoma

Abstract: It has been suggested that particle size plays an important role in determining the genotoxicity of gold nanoparticles (GNPs). The purpose of this study was to compare the potential radio-sensitization effects of two different sized GNPs (3.9 and 37.4 nm) fabricated and examined in vitro in Lewis lung carcinoma (LLC) as a model of non-small cell lung cancer through use of comet and clonogenic assays. After treatment with 2Gy X-ray irradiation, both particle sizes demonstrated increased DNA damage when compared… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 31 publications
1
20
0
Order By: Relevance
“…Cells were passaged for subculturing by first aspirating the culture medium with a pipette, rinsing with 1× phosphate buffered saline (PBS, Thermo Fisher Scientific, Waltham, MA, USA, SH30256FS), aspirating off the PBS, then rinsing with 0.25% trypsin-0.53 mM EDTA solution (Thermo Fisher Scientific, Waltham, MA, USA, 25-200-056), and then they were neutralized with complete growth media consisting of Dulbecco's modified Eagle's medium (DMEM, ATCC ® , Manassas, VA, USA) with 10% fetal bovine serum (FBS, USDA approved, ATCC ® , Manassas, VA, USA), and 1% Penicillin-Streptomycin (10,000 U/mL, Thermo Fisher Scientific, Waltham, MA, USA). Cells were modified to be luciferase-expressing (LLC-Luc), as previously described [54] through use of plasmid pLenti PGK V5-LUC Neo [63] (Addgene, Cambridge, MA, USA) which was packaged in lentiviral particles and performed at the Baylor College of Medicine (BCM) vector core facility. For the luciferaseexpressing cells, 1% Geneticin (Thermo Fisher Scientific, Waltham, MA, USA) was added to the media to maintain culture.…”
Section: Maintenance and Llc Subculturementioning
confidence: 99%
See 1 more Smart Citation
“…Cells were passaged for subculturing by first aspirating the culture medium with a pipette, rinsing with 1× phosphate buffered saline (PBS, Thermo Fisher Scientific, Waltham, MA, USA, SH30256FS), aspirating off the PBS, then rinsing with 0.25% trypsin-0.53 mM EDTA solution (Thermo Fisher Scientific, Waltham, MA, USA, 25-200-056), and then they were neutralized with complete growth media consisting of Dulbecco's modified Eagle's medium (DMEM, ATCC ® , Manassas, VA, USA) with 10% fetal bovine serum (FBS, USDA approved, ATCC ® , Manassas, VA, USA), and 1% Penicillin-Streptomycin (10,000 U/mL, Thermo Fisher Scientific, Waltham, MA, USA). Cells were modified to be luciferase-expressing (LLC-Luc), as previously described [54] through use of plasmid pLenti PGK V5-LUC Neo [63] (Addgene, Cambridge, MA, USA) which was packaged in lentiviral particles and performed at the Baylor College of Medicine (BCM) vector core facility. For the luciferaseexpressing cells, 1% Geneticin (Thermo Fisher Scientific, Waltham, MA, USA) was added to the media to maintain culture.…”
Section: Maintenance and Llc Subculturementioning
confidence: 99%
“…We hypothesize that by controlling the adsorption of proteins on the GNP surface, we can modulate the zonal distribution of the particles in the tumor. We previously demonstrated that our spherical GNPs have a significant radio-sensitization property in vitro [54], inducing DNA damage in Lewis lung carcinoma (LLC) cells, as well as excellent properties as contrast agents for computed tomography (CT) in vivo [55]. However, these preliminary studies did not consider the hypothesis that surface protein adsorption can affect the intratumoral distribution and retention of the particles.…”
Section: Introductionmentioning
confidence: 96%
“…PFGE is there for better to be used for quantitative purposes. Gel electrophoresis was already used in several studies concerning metallic NP (especially AuNPs) radiosensitization [178,179]. 6.…”
mentioning
confidence: 99%
“…Cells were passaged for subcultured by first aspirating the culture medium with a pipette, rinsing with 1x phosphate buffered saline (PBS, Thermo Fisher Scientific, Waltham, MA, USA, SH30256FS), aspirating off the PBS, then rinsing with 0.25% trypsin -0.53 mM EDTA solution (Thermo Fisher Scientific, Waltham, MA, USA, 25-200-056) and the neutralized with complete growth media consisting of Dulbecco's Modified Eagle's Medium (DMEM, ATCC®, Manassas, VA, USA) with 10% fetal bovine serum (FBS, USDA approved, ATCC®, Manassas, VA, USA), and 1% Penicillin-Streptomycin (10,000 U/mL, Thermo Fisher Scientific, Waltham, MA, USA). Cells were modified to be luciferase expressing (LLC-Luc) as previously described [54] through use of plasmid pLenti PGK V5-LUC Neo [63] (Addgene, Cambridge, MA, USA) which was packaged in lentiviral particles andperformed at the Baylor College of Medicine (BCM) vector core facility. For the luciferaseexpressing cells, 1% Geneticin (Thermo Fisher Scientific, Waltham, MA, USA) was added to the media to maintain culture.…”
Section: Maintenance and Llc Subculturementioning
confidence: 99%
“…We hypothesize that by controlling the adsorption of proteins on the GNP surface, we can modulate the zonal distribution of the particles in the tumor. We previously demonstrated that our spherical GNPs have a significant radiosensitization nature in vitro [54], inducing DNA damage in Lewis Lung Carcinoma (LLC) cells as well as excellent properties as contrast agents for Computed Tomography (CT) in vivo [55]. However, these preliminary studies didn't consider the hypothesis that surface protein adsorption can affect intratumoral distribution and retention of the particles.…”
Section: Introductionmentioning
confidence: 97%